Evidence of Distinct Genetic Stocks of the Bottlenose Wedgefish (Rhynchobatus australiae) in the Indo-West Pacific - Simwanza, Rehema J.; Rumisha, Cyrus (Tanzania Journal of Science, 2023)
Populations of the bottlenose wedgefish (Rhynchobatus australiae) in the Indo-West Pacific (IWP) have declined by nearly 80% in recent decades. In response, IWP countries are establishing sanctuaries to provide refuge for the fish. However, little is known about the genetic stock structure of the fish in the region. Hence, this study analysed partial sequences (610 base pairs) of the cytochrome oxidase subunit (COI) gene from eight bottlenose wedgefish populations in the IWP to assess the genetic stock structure of the fishery. The sequences revealed that Western Indian Ocean (WIO) populations are genetically distinct from those in the West Pacific (WP) (FCT 0.24, p = 0.01) and Australia (FCT = 0.88, p = 0.01). Similarly, WP populations were genetically distinct from Australian populations (FCT = 0.42, p = 0.01). This suggests that the IWP contains three genetically distinct stocks of the bottlenose wedgefish: the WIO, WP, and Australia. The indices of genetic diversity and population size showed that the WIO stock has low genetic diversity and population size when c=ompared to the WP and Australia. This shows that efforts to establish elasmobranch sanctuaries in the IWP should take into account the three identified stocks, with priority given to the WIO. Keywords: Restricted gene flow, genetic connectivity, elasmobranch sanctuaries, Indo-West Pacific Ocean